2004
DOI: 10.1007/s00170-004-2118-3
|View full text |Cite
|
Sign up to set email alerts
|

Economical delivery strategies of products in a JIT system under a global supply chain

Abstract: This study supplies an optimal total cost model, including approach I and approach II, to manufacturers with several assemblers in the same area to decide the most economical product delivery strategy in the global just-in-time (JIT) system. In approach II, manufacturers deliver products to downstream assemblers via a JIT system with third party logistics (3PL) support. There is a distinction between approach I and approach II according to whether or not the delivery quantity is limited to economical delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Rather, they utilize the extended transport networks of global 3PL's in various regions. This partnering with 3PL's streamlines the JIT operations and contributes to lean and agile supply chain (Kreng & Wang, 2005).…”
Section: Emergence Of 3pl Partnerships As a Global Jit Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, they utilize the extended transport networks of global 3PL's in various regions. This partnering with 3PL's streamlines the JIT operations and contributes to lean and agile supply chain (Kreng & Wang, 2005).…”
Section: Emergence Of 3pl Partnerships As a Global Jit Requirementsmentioning
confidence: 99%
“…In the era of global supply chain, companies buy parts and components from abroad. Then, those imported parts and components are oftentimes consolidated by 3PLs that are within the driving distance from a manufacturer (Kreng & Wang, 2005). In a foreign manufacturing environment, a cluster is often formed through physical proximity for JIT manufacturing (Wood and Murphy, 2004).…”
Section: Emergence Of 3pl Partnerships As a Global Jit Requirementsmentioning
confidence: 99%
“…References to JIT material flow in the SC context are scarce, but are increasing during last years. Among them, it is worth mentioning the works by Gargouri and Hammadi (2002), Olhager (2002), Vergara et al (2002), Chiu and Huang (2000), Kim and Ha (2003), Rubiano and Crespo Marquez (2003), Aigbedo (2004), Wang et al (2004), Kreng and Wang (2005), Liberopoulos and Koukoumialos (2005), Mistry (2005), Takahashi et al (2005), Wang and Sarker (2005), Wang and Sarker (2006), Wong and Johansen (2006), Zhao et al (2007) and Hopp (2008). Gargouri and Hammadi (2002) focus on an agro‐food environment where there is an unpredictable and seasonal demand.…”
Section: Materials Flow Control In the Scmentioning
confidence: 99%
“…The problem is modelled as a LP model in order to minimise the total costs. Kreng and Wang (2005) discuss two different JIT systems under a global SC according to whether the delivery of products is limited or not to their economic lot size. Liberopoulos and Koukoumialos (2005) state that advance demand information (ADI) systems may acquire a great importance in the SC context.…”
Section: Materials Flow Control In the Scmentioning
confidence: 99%
“…These models considered multiple deliveries of an order, but they did not emphasize the logistics center as a medium, in order to reach the purpose of both parties making large batches and transporting in turn. Kreng and Wang (2005) suggested that manufacturers can optimize their total cost by deciding whether or not to cooperate with third party logistics (3PL) and arrive at their optimal production lot size. 3PL will also occupy a much more important position in the JIT system under a global supply chain.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%